Understanding the role of RNA nucleases in human disease - Brolih, S (2021)
Congenital dyserythropoietic anaemia type-I (CDA-I) is a rare inherited disorder of erythropoiesis, in which patient erythroblasts uniquely display a pathognomonic pattern of heterochromatin, referred to as ‘spongy’ heterochromatin. The molecular basis of CDA-I remains unknown. Most cases of CDA-I are caused by mutations in a protein of unknown function, termed Codanin-1. However, the recent identification of a second disease gene in CDA-I, namely C15orf41, has marked a breakthrough in providing new insights into CDA-I. This study describes the previously-uncharacterised protein C15orf41 as a novel RNA exonuclease that associates in vivo and in vitro with Codanin-1. Using the newly generated CDA-I disease model in an erythroid-specific HUDEP-2 cell background, C15orf41 and Codanin-1 complex formation is determined at physiologically relevant levels. This interaction is then also confirmed in vitro. The C15orf41-Codanin-1 complex is a versatile RNA nuclease complex, able to digest a variety of RNA structures. We also show the association and nucleolytic activity of C15orf41-Codanin-1 are disrupted by the introduction of CDA-I patient mutations p. Y94C and p. L178Q in C15orf41. This suggests a direct link between the disease phenotype observed and C15orf41’s novel RNAse activity, a potential new target for alternative treatment development.